The relationship between choroidal and photoreceptor layer thickness with visual acuity in highly myopic eyes - Mahmud, Mazaya; Ahem, Amin; Bastion, Mae-Lynn Catherine; Omar, Rokiah; Mohammed Nawi, Azmawati; Razak, Norsyariza; Mohd Satali, Adib; Mohd Khialdin, Safinaz; Md Din, Norshamsiah (Frontiers Media, 2022)
Purpose: The aim of this study was to evaluate the choroidal and photoreceptor thickness in highly myopic eyes and its correlation with visual acuity. Methods: This is a cross-sectional, observational study involving 57 eyes of 57 highly myopic subjects [spherical equivalent ≥ –6 diopters (D) or axial length ≥ 26 mm] seen in a tertiary institutional center. Eyes with any clinical evidence of maculopathy or amblyopia were excluded. All subjects underwent a refraction assessment, visual acuity, axial length measurement using the IOL Master, and full ocular assessment. Eyes were imaged using Spectralis Optical Coherence Tomography by one experienced operator. Two independent investigators manually measured subfoveal choroidal thickness (SFCT) and foveal photoreceptor thickness (FPT). Results: The mean SFCT was 195.88 ± 87.63 μm (range: 32–373) and mean FPT was 96.68 ± 11.23 μm (range: 67–100), after correction for ocular magnification. The best corrected visual acuity (BCVA) in LogMAR was negatively correlated with SFCT (r = –0.510, p = 0.001) and FPT (r = –0.397, p = 0.002) and positively correlated with age (r = 0.418, p = 0.001) and axial length (r = 0.551, p = 0.001). Multiple linear regression analysis showed that age, axial length, and corrected FPT were significant risk factors for poorer BCVA (p = 0.021, < 0.001, and 0.02, respectively). Conclusion: FPT, age, and axial length are significant moderate predictive factors for poorer visual acuity in highly myopic eyes without myopic maculopathy. Thinner SFCT does not translate into poorer vision.